MANAGEMENT INSOMNIA IN ELDERLY - Hindri Astuti, Ni Made (E-Jurnal Medika Udayana; vol 2 no4 (2013):e-jurnal medika udayana, 2013)
Insomnia is common problem in elderly. Sleep problem in the elderly are often mistakenly considered a normal part of aging. Insomnia, the most common sleep disorder, is a subjective report of insufficient or nonrestorative sleep despite adequate opportunity to  sleep.  Despite  the  fact  that  more  than  50%  of  elderly  people  have insomnia, it is typically undertreated. There are two management insomnia in elderly. We can use nonpharmacologic and pharmacologic treatment of insomnia in elderly. The goal of therapy is reduce symptom, improve patient productivity and cognition   to improve quality of life for the patient and family.
Keywords: management, insomnia, elderly